The panda puzzle - Roy, Ron, 1940-; Gurney, John (New York : Random House, 2002)
Dink, Josh, and Ruth Rose investigate the kidnapping of the new baby panda at the petting zoo
"A stepping stone book."
2.8
006-009
Keywords: Giant panda -- Fiction; Pandas -- Fiction; Zoos -- Fiction; Mystery and detective stories